Pregled različnih metod in pristopov družboslovnega raziskovanja - Šilih, Majna (Mednarodno inovativno poslovanje, 2023)
Various methods and approaches are used in social science to collect and analyze data, which enable social scientists to understand human behavior and social phenomena. Methods and approaches have developed and changed over time and especially, due to the rapid progress of technology, they have undergone a transformation in recent decades. New technologies make it possible to collect and analyze data in an even more comprehensive andinformative way, as they are able to process ever-increasing amounts of available data, which in turn helps to discover patterns, trends, connections and affects the understanding of human life and social phenomena
Keywords: changes in social science research; Družboslovno raziskovanje; kvalitativno raziskovanje; kvantitativno raziskovanje; metode raziskovanja; qualitative research; quantitative research; research methods; social science research; spremembe družboslovnega raziskovanja